INDUKSI KETAHANAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) TERHADAP CEKAMAN KEKERINGAN DENGAN APLIKASI BEBERAPA DOSIS BORIC ACID DAN SODIUM SILICATE - , ISSUKINDARSYAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research aims were 1) to determine the mechanical and physiological responses of oil palm tissues to the applications of B and Si and 2) to determine the optimal doses of B and Si that induce the oil palm seedling to drought resistance. The research was arranged in Randomized Complete Block Design (RCBD) factorial with three blocks as replication. The first factors were the doses of B, namely 0, 0.17, 0.44, 0.87, 1.31 and 1.75 g/crop. The second factors were the doses of Si, namely: 0, 1.15, 2.31, 3.46, and 4.61 g/crop. Observations were done on several variables of microclimate, plant growth, physiological activity, anatomy and morphology of crops as well as B and Si concentrations in crop tissues. Data were analyzed using analysis of variance (ANOVA) at 5% levels, and continued using least significant difference test (LSD). The optimum doses of B and Si that able to increase oil palm resistance to drought stress were determined using regression analysis. Morphological and physiological characters of oil palm seedlings that have direct and indirect effects to the drought stress were determined through path analysis. The results showed that the application of B was able to induce resistance of oil palm seedlings to drought stress through physiological mechanisms, namely an increase in the accumulation of proline, phenol and antioxidant activities as well as the minimization of the free-radical activity in the form of H2O2. Meanwhile, Si applications on oil palm seedlings were able to induce resilience to drought stress through the structural reinforcement (thickening) of root cell walls indicated by the increase of root firmness. The optimal doses of B that to induce the resistance of oil palm seedlings to drought stress was 0.44 to 0.83 g/crop, meanwhile the optimal doses of Si could not be found until 4.61 g applications/crop.